2008
DOI: 10.1038/jp.2008.112
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal characteristics of extremely low birth weight infants who die in the first day of life

Abstract: Objective: To determine changes over time in the characteristics of early extremely low birth weight non-survivors (E-ELBW-NS), maternal characteristics and perinatal management, and the documentation of perinatal consultations.Study Design: We conducted a chart review of infants <750 g who died within 24 h divided into two epochs: 1 January 1995 to 31 December 1999 and 1 January 2000 to 31 December 2005. Maternal and neonatal characteristics, delivery room resuscitation, post-resuscitation care, and documenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The theme of worse care in minorityserving hospitals recurs throughout this review. * Although these findings could be secondary to other confounders such as socioeconomic differences in influencing disparate outcomes, [39][40][41][42][43]45,46 we also found racial and/or ethnic disparities across processes 9,21,22,24,[27][28][29][30][31]33,37 that disadvantage infants of color. This indicates that disparities may be under the control of providers and amenable to improvement by using available QI tools.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The theme of worse care in minorityserving hospitals recurs throughout this review. * Although these findings could be secondary to other confounders such as socioeconomic differences in influencing disparate outcomes, [39][40][41][42][43]45,46 we also found racial and/or ethnic disparities across processes 9,21,22,24,[27][28][29][30][31]33,37 that disadvantage infants of color. This indicates that disparities may be under the control of providers and amenable to improvement by using available QI tools.…”
Section: Discussionmentioning
confidence: 70%
“…Three articles were focused on overall morbidity or mortality, revealing contradictory trends. In 2 articles, 42,43 the researchers indicated a disadvantage for infants of color. Jacob et al 42 found that Alaskan Native infants had higher rates of NEC, retinopathy of prematurity (ROP), and chronic lung disease compared with non-Native infants.…”
Section: Overall Morbidity or Mortalitymentioning
confidence: 99%